Preventing suicide in indigenous communities. Issue 1 (January 2017) - Hatcher, Simon; Crawford, Allison; Coupe, Nicole
Abstract : Purpose of review: To provide an update on recent studies on suicide prevention in indigenous populations with a focus on recently colonised indigenous peoples in Canada, the United States, Australia and New Zealand. Recent findings: There have been several recent reviews on suicide prevention in indigenous populations with high suicide rates. However most of them describe the problem and there is little new that is available on effective interventions. One randomized controlled trial of a package of measures focusing on cultural identity in Maori who had recently self-harmed compared to usual care found little effect on suicidal behavior but it did significantly reduce presentations to hospital for any reason after one year. Summary: The reasons for the limited evidence include a lack of ring fenced funding and a lack of research infrastructure; the problem of high rates of suicide but small numbers; and the difficulty in creating effective collaborations between researchers and communities. Potential solutions include identifying specific research funding; improving capacity in indigenous research; putting effort into accurate identification and recording of ethnicity; and thinking about the problem of suicide in recently colonised populations as a global problem to enable large scale high quality studies to take place.